S4_5 If You Liked It, You Should Have Put A Ring On It - Best, Joel Thomas; Duggan, Matt Jackson; Croxford, Saul Marcus Benedict (Physics Special Topics, 2017)
In this paper, we explore the potential energy to be harnessed by constructing a Dyson Ring, and produce a ball-park figure of the associated costs. We find that there is the possibility to collect approximately 6 ×1010 Watts of power, and that an initial investment of £50 billion could suffice to install such a structure.